2012
DOI: 10.5114/aoms.2012.27275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-week administration of simvastatin in different doses on heart rate and blood pressure after metoprolol injection in normocholesterolaemic and normotensive rats

Abstract: IntroductionStatins and β1-adrenergic antagonists are well established in cardiovascular events therapy and prevention. The previous study showed that statins might impact on β-adrenergic signalling and blood pressure in a dose-dependent manner. The aim of the study was to evaluate the impact of 4-week administration of simvastatin given at different doses on the heart rate and blood pressure after injection of metoprolol in rats.Material and methodsThe experiments were performed in normocholesterolaemic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Taking into consideration the increase in HTN prevalence and the complex pathogenesis mechanism, targeting inflammation as a possible antihypertensive therapy is a new option. Evidence showed that several cardiovascular drugs like statins, ACEI, ARBs, and calcium channel blockers lowered blood pressure and serum inflammatory cytokines concentrations [54, 162, 164, 167, 171179]. Even if antihypertensive effects of monoclonal antibodies remain controversial, some experimental animal studies showed that IL-6 inhibition in hypertensive specimens decreased myocardial fibrosis and reduced albuminuria, emphasizing the role of the proinflammatory cytokine in developing end-organ damage [180].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into consideration the increase in HTN prevalence and the complex pathogenesis mechanism, targeting inflammation as a possible antihypertensive therapy is a new option. Evidence showed that several cardiovascular drugs like statins, ACEI, ARBs, and calcium channel blockers lowered blood pressure and serum inflammatory cytokines concentrations [54, 162, 164, 167, 171179]. Even if antihypertensive effects of monoclonal antibodies remain controversial, some experimental animal studies showed that IL-6 inhibition in hypertensive specimens decreased myocardial fibrosis and reduced albuminuria, emphasizing the role of the proinflammatory cytokine in developing end-organ damage [180].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients tend to have increased interleukin 1 β secretion under Ang II stimulation compared to normotensive individuals. Simvastatin therapy reduced Il-1 β levels independently of lipid-lowering effects [167].…”
Section: Inflammation As a Potential Therapeutic Target In Arteriamentioning
confidence: 99%
“…21,22 The effect of statins on BP have been studied in a number of clinical trials which, however, provided conflicting results. 2331 Studies on the potential hypotensive effect of statins have also provided conflicting results. 2731…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that simvastatin or pravastatin did not enhance the blood pressure–lowering action of angiotensin‐converting enzyme inhibitors, AT 1 receptor blockers, calcium channel blockers, or beta blockers .…”
Section: Discussionmentioning
confidence: 99%
“…However, the results regarding blood pressure-lowering effect of statins are conflicting [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%